2004
DOI: 10.1016/j.electacta.2004.01.076
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir–Blodgett films of different ionomeric polymers deposited on electrode surfaces

Abstract: This paper shows the possibility to apply the Langmuir-Blodgett (LB) techniques for the preparation of ultrathin films of various ionomeric polymers, namely Nafion ® (perfluorinated cation-exchanger), Tosflex ® (perfluorinated anion-exchanger) and Eastman AQ55 ® (polyestersulfonated cation-exchanger). The pressure-area isotherms and the condensation degree of the interfacial films depend on the chemical structure of the ionomer and on the nature of the electrolyte dissolved in the subphase. The addition of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…Moreover, it was shown that Nafion LB or Nafion LS films present other peculiar characteristics different from those of recasted Nafion, as recently outlined by electrochemical studies [20,21] also in combination with epifluorescence microscopy [22]. Nafion LB films are indeed very homogeneous and compact [18] and being very thin, they present very short response time to electrochemical switching [22].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, it was shown that Nafion LB or Nafion LS films present other peculiar characteristics different from those of recasted Nafion, as recently outlined by electrochemical studies [20,21] also in combination with epifluorescence microscopy [22]. Nafion LB films are indeed very homogeneous and compact [18] and being very thin, they present very short response time to electrochemical switching [22].…”
Section: Introductionmentioning
confidence: 85%
“…First of all, the deposition of Langmuir monolayers on electrodes allows one to build continuous permselective coatings as thin as few nanometers [17][18][19]. Moreover, it was shown that Nafion LB or Nafion LS films present other peculiar characteristics different from those of recasted Nafion, as recently outlined by electrochemical studies [20,21] also in combination with epifluorescence microscopy [22].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This could be obtained by preparing ultrathin bi-layers, by resorting, for instance, to Langmuir-Blodgett techniques which can be employed for preparing ionomer permselective films as thin as few nanometers [44,45]. Further studies on such a possibility are presently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, the arrangement of polymers in films is more attractive than the use of low molecular weight materials because of their widely demonstrated device applications [12]. In the case of electrochemical applications, three kinds of polymers can be distinguished in terms of the redox group position in the polymer: (i) electroactive polymers, the redox group is in the lateral chain [13]; (ii) conducting polymers, the redox group is in the main chain [14,15]; (iii) ionomeric polymers, the electroactive specie is an ion [16,17].…”
Section: Introductionmentioning
confidence: 99%